ISOLATION AND CHARACTERIZATION OF LIPOLYTIC BACTERIA FROM OIL CONTAMINATED SOIL FROM PETROL BUNK AT SOUTHEAST BANGALORE. - Sahu, Ajay Kumar; Nemani, Rahul; Acharya, Prangya Prangya; Sinha, Rupali; Sengupta, Subhranil; Pradhan, Bibekananda (Asian Journal of Pharmaceutical Research and Development, 2019)
The isolation of oil contaminated sites and gravimetric analysis of degradation in which, two bacterial formed maximum clearing zones on minerals salt medium. An increase in cell number indicating that the bacterial isolation was responsible for the oil degradation .the collected oil contaminated sites at kormongala, Indra nagar, MTTC culture , micrococcus spp., Bacillus spp., pseudomonas spp., which are able to utilize the oil in soil as carbon sources, were added to oil contaminated soil sample , the growth profiles were determined by monitoring the optical density, dry weight and Ph of the culture utilizing lubricating oil as sole sources of carbon, Bushnell Haas media supplemented with petrol, kerosene and diesel as sole carbon sources was used for isolation of bacteria capable of degrading these petroleum fractionates. From three soil sample and two water sample, a total of nine bacterial strains were isolated capable of degrading petrol, kerosene and diesel with varying tolerance capacities, the isolates were identify by using standard biochemical test and morphological studies and it was determined that these strains belong to six bacterial genera .the present study suggest that the isolated bacterial species could be employed for bioremediation in environment polluted with petroleum and its products, indigenously from the soil and water contaminated with crude oil in the vicinity of oil drilling well were found to be most efficient crude oil utilize as turbidity observed by spectrophotometrically. In the various study of lipolytic bacteria concluded that the taken of oil contaminated soil from from petroleum bunk and to identify their biochemical characterization by using various sources. How it’s helpful for characterize by using of lipolytic bacteria